2002
DOI: 10.1520/jfs15211j
|View full text |Cite
|
Sign up to set email alerts
|

Ecstasy (MDMA) Deaths in New York City: A Case Series and Review of the Literature

Abstract: MDMA ("ecstasy") has gained renewed popularity as a drug of abuse. To access the epidemiology and causes of death of MDMA-positive fatalities, all deaths investigated by the OCME that tested positive for MDMA (22 deaths) between January 1997 and June 2000 were reviewed. There were three deaths in each 1997 and 1998, eleven in 1999, and five in the first part of 2000. Of these 22 deaths, 13 were due to acute drug intoxications, 7 due to mechanical injury (blunt trauma, gunshot wounds), and 2 due to a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 52 publications
1
39
0
7
Order By: Relevance
“…Larger-scale reviews conducted in the UK [37] and the USA [38] have focused only on deaths where ecstasy was detected in toxicology, without discussing the role it played in relation to the death. One US review reported that death due to MDMA toxicity alone was relatively rare (2 in a 4-year period) [39] and that pre-existing cardiac pathology and multiple drug toxicity was more common among these deaths. Nevertheless, the variable nature of the contents of MDMA tablets clearly increases the risks of adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Larger-scale reviews conducted in the UK [37] and the USA [38] have focused only on deaths where ecstasy was detected in toxicology, without discussing the role it played in relation to the death. One US review reported that death due to MDMA toxicity alone was relatively rare (2 in a 4-year period) [39] and that pre-existing cardiac pathology and multiple drug toxicity was more common among these deaths. Nevertheless, the variable nature of the contents of MDMA tablets clearly increases the risks of adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Certain support measures should also be included, such as: maintaining the permeability of the respiratory tract, ventilatory support, supplying the patient with 100% oxygen, maintaining urinary output and supplying cold fluids (via the stomach, gall bladder and veins) in cases of hyperthermia. The increase in temperature should be treated with urgency, since untreated cases may result in rhabdomyolysis and disseminated intravascular coagulation [24][25][26] . Although dantrolene is recommended as a treatment option, in cases of hyperthermia induced by MDMA, there is little evidence in the literature supporting its effectiveness 11 .…”
Section: Quadro I -mentioning
confidence: 99%
“…Inclui medidas de suporte como a manutenção da permeabilidade das vias aéreas, assistência ventilatória, administração de oxigênio a 100%, manutenção do débito urinário e infusão de líquidos frios (vias gástrica, vesical e venosa) nos casos em que há hipertermia. A elevação da temperatura deve ser tratada agressivamente, pois em casos não tratados, podem ocorrer rabdomiólise e coagulação intravascular disseminada [24][25][26] . Apesar do dantrolene ser indicado como opção terapêutica nos casos de hipertermia induzida por MDMA, existem poucas evidências que apóiem sua eficácia 11 .…”
Section: Introductionunclassified
“…Weitere 11 nicht eindeutig geklärte Fälle dürften ebenfalls auf die Einnahme von Amphetaminen zurück zu führen sein; 9 Personen verstarben nach dem Konsum von Ecstasy [4]. Gill et al berichten von 22 Todesfällen durch Ecstasy in den Jahren 1997-2000 allein in New York [6]. Die Autoren berichten von über 45 Todesfällen in der Literatur durch Ecstasy-Intoxikationen bis zur Publikation des Beitrags [6].…”
Section: Historikunclassified